Analisis Terhadap Kepemimpinan Perempuan Ditinjau Dalam Perspektif Hukum Islam - Muhammad Arba’in; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Female leadership in the perspective of Islamic law is a controversial issue among Muslims. Some scholars see that religion (Islam) forbids women from becoming leaders, the reason being that the text of the verses of Al-Qur'an and Al-Hadist explicitly state such a ban. But some scholars hold the opposite view, that legitimate women become leaders, the reason the text of the verses of Al-Qur'an and Al-Hadist must always be interpreted (understood) contextually, not merely textual, meaning that every text must be understood in the context of social-political sphere. The sociopolitical context that developed during the period of the fall of the texts was very different from the present social context. In the context of modern times, there is no reason to forbid women to be leaders.The purpose of writing this thesis namely: First, To know the position of women in Indonesian law, Second, To know the leadership of women in Indonesia is appropriate if associated with Islamic Law.This type of research is a normative juridical study. This research is conducted by examining the literature, collection of books or writings, or secondary data that still have to do with Women's Leadership in Islamic Law Perspective. From the results of research problems there are two main things that can be concluded, First, the position of women in Islamic law is very noble and received considerable attention and occupy a very commendable poisisi, even many verses in the Qur'anic texts praise the women. Secondly, the scholars agree to allow women to be judges or leaders if examined in fiqh consideration and see the current political condition of politics.Keywords: Leadership - Women - Perspective - Law - Islam